PERAN KONSELOR TERHADAP PERILAKU HIDUP BERSIH DAN SEHAT ANAK USIA DINI DI MASA PANDEMI COVID-19: konselor, sehat, anak, covid-19 - Adine Rasendri Hania; Adela Tsamrotul Fikriyah (AL IHSAN: Jurnal Pendidikan Islam Anak Usia Dini, 2021)
Clean and healthy behavior for early childhood is carried out for the benefit of children and their families. Children are very vulnerable to transmission of the virus, especially during the COVID-19 pandemic. The role of parents as the main actors to familiarize and set an example for children to always live clean and children's school teachers as counselors for children at school. This study aims to briefly describe the role of counselors in children's clean and healthy living behavior during the COVID-19 pandemic and in this new normal era. The research method uses the library method. The object of this research is obtained from scientific journals, theses, books, articles and other documents. The results showed that the role of counselors, parents, and teachers is needed to always give the best to children by maintaining cleanliness, always washing hands after carrying out any activities, utilizing individual defensive gear by continually wearing a veil, and expanding the youngster's resistant framework by giving nutritious food, counseling a nutritionist, taking kids to rest consistently and practicing routinely. Also, consistently cause youngsters to feel glad despite the fact that learning at school is redirected to internet learning, so kids don't feel exhausted.